Sequential Leaching Of Malaysian’s Ion Adsorption Clay Rare Earth Element - Haris, Nuradrina (Universiti Sains Malaysia, 2022)
Ion adsorption clay rare earth has been getting known for many applications to the industry. Malaysia has the enough potential of RE-bearing rocks for formation of ion adsorption clay. However, there are not enough extensive studies on Malaysian’s ion adsorption clay. Hence, the purposes of this research are to determine the physical and chemical characteristics of Malaysian’s ion adsorption clay and determine the potential extraction of REE by sequential extraction. Oriented clay sample was prepared from separation of clay minerals to subject the sample for XRD, and SEM. The chemical composition and trace elements of the sample done by XRF and ICP-MS. The ore is mainly composed with high concentration of Cerium. The ion adsorption clay was also composed with silica, quartz and the clay minerals present in the sample are included with yugawaralite, berlinite and montmorillonite. Ammonium sulfate leaching (1S) and 5-step (5S) sequential extraction (SE) were conducted on the samples to determine the potential extraction of and extraction efficiency. The results reported that ammonium sulfate leaching can leach almost all the REE compared to sodium acetate used in 5S. this indicates that ammonium sulfate leaching is suitable leaching reagent to extract REE from ion adsorption ore. The ion adsorption ore also has the potential to recover La, Nd and Ce by ammonium sulfate. Zeta potential of clay particle is done on residue from each extraction steps. Ion adsorption clay leached by ammonium sulfate had the highest electronegative value of zeta potential, which was-23.5 mV. This indicates that the clay particles leached by ammonium sulphate had high dispersion which does not beneficial of good soil formation.